DYNASTY POLITICS AND THE FUTURE OF LOCAL DEMOCRACY IN BALI: A CASE STUDY OF THE 2024 ELECTION - Pinatih, I Gusti Ayu Agung Dewi Sucitawathi (Sosiohumaniora, 2026)
Dynastic politics is a common phenomenon during general elections, both at the central and regional levels. This dynastic political pattern can be found in the selection of legislative candidates (caleg) and executive candidates (regional heads) which are colored by family relationships, such as parent-child, in-law-son-in-law, husband-wife. This study aims to capture the dynastic political pattern that occurs in Bali, including the unique ways in which it maintains its dominance, as well as the implications of dynastic politics on the quality of local democracy. The research method used is library research as the primary technique in data collection and analysis. Data sources in this study include two main categories: first, scientific journals or books, that discuss the phenomenon of dynastic politics empirically and theoretically according to different local contexts. Second, media content analysis by examining the monitoring of election results by independent institutions and socio-political narratives developing within the community. The research findings indicate that the survival of dynastic politics in Bali is determined not only by political party networks, but also by strong political networks based on customs and culture. These traditional political networks provide parties with the option to maintain or reverse dynastic politics. Negative implications include a thriving political oligarchy, hampered leadership regeneration, and decreased leadership accountability. Potential positive implications include the ability of the authorities to maintain political stability (support) and the assurance of the continuity of previous government programs.